Age and drinking-related differences in the memory organization of alcohol expectancies in 3rd-, 6th-, 9th-, and 12th-grade children. - Dunn, Michael E.; Goldman, Mark S. (Journal of Consulting & Clinical Psychology, 1998)
To advance the theoretical modeling of the development of alcohol expectancies as a parallel processing memory network, this study assessed expectancies and alcohol consumption of 2,324 children in Grades 3, 6, 9, and 12 from a large suburban-rural school district. Individual-differences scaling (INDSCAL), a variant of multidimensional scaling, mapped expectancies into a hypothetical memory network format, and preference mapping (PREFMAP) modeled hypothetical paths of association within this network. Throughout this age range, older and higher drinking youth appeared to associate positive and arousing effects with alcohol cues, in contrast to lower drinking children, who appeared to mainly associate undesirable effects. These drinking-related differences in the organization of expectancy information are discernible well before onset of regular drinking habits and may influence the development of drinking in adolescence. Reprinted by permission of the publisher.